Evaluation of the musculoskeletal disorders and its risk factors in the workers of an agricultural equipment- manufacturing plant - M Mostaghaci; Z Salimi; M Javaheri; Sf Hoseininejad; M Salehi; Mh Davari; Ah Mehrparvar (طب کار)
Abstract Background: Musculoskeletal disorders (MSDs) are caused by chronic and long-term exposure to ergonomic factors or by an acute injury. MSDs are the most important cause of work hour loss and medical costs in the workplace. In this study, ergonomic risk factors and frequency of MSDs of workers of an agricultural equipment-manufacturing plant were evaluated. Methods: In a cross-sectional study 70 workers were evaluated. Nordic questionnaire was used for evaluation of musculoskeletal disorders and RULA and QEC methods were used for ergonomic risk assessment. Data was analyzed using SPSS (ver. 17). Results: Mean age and employment duration of the workers was 32.75±3.6 and 6.45±7.9, respectively. Frequency of MSDs in these workers was 40.3%. Frequency of the disorders in each body part was: back (12.8%), knee (8.7%), hand (7.8%), neck (6%), and shoulder (5%). RULA score for welding and painting units was 7 and this measure for warehouse and assembly unit was 6 which are in the action level of 3 and 4, respectively. QEC score in 21.3% of workers was between 51 and 70, and 8.2% had a score more than 70, and both need ergonomic intervention. Conclusion: A considerable percent of workers in this factory work in a non-safe ergonomic situation and the frequency of musculoskeletal disorders are high among them which needs a proper ergonomic intervention.